Laser in situ synthesis of gradient aluminides in metal matrix composite during DMD process. (2015) - Shishkovsky, Igor; Kakovkina, Nina; Missemer, Floran
The suitability of direct metal deposition process of exothermic powders (Ni-Al, Ti-Al, Fe-Al systems), traditionally used in the self-propagating high-temperature synthesis technology, is described. Owing to the synthesis of new intermetallic phases, the overlapping of laser in situ synthesis and layerwise deposition processes makes it possible both to obtain more durable parts of complex shape, and to enlarge the functional resource of these functional-graded structures. Besides, relationships between the main laser deposition parameters and the intermetallic phase structures of the built-up objects were studied. In our research we applied optical microscopy, X-ray analysis, microhardness measurement and SEM with EDX analysis of the laser-fabricated intermetallics.